Sustainable Leadership in International Schools: A Stakeholder Alignment Perspective - Peng, Yihong; Alias, Bity Salwana; Wan, Xinyu; Mansor, Azlin Norhaini (Journal of International Students, 2026)
This study investigates how international schools in Shanghai address sustainability challenges through stakeholder-driven strategies. Drawing on stakeholder theory, the research examines how parents, teachers, and school leaders perceive and prioritize strategic responses to complex institutional pressures. A qualitative multiple-case design was employed, involving semistructured and unstructured interviews with 16 participants (3 parents, 5 teachers, and 8 school leaders), and data were analyzed using qualitative content analysis. The findings identify four interrelated strategy domains: student-, teacher-, parent-, and system-focused approaches. While student-focused strategies are most visible due to their direct impact, the study reveals that effectiveness is not inherent in individual strategies but emerges from their alignment across stakeholders. Teacher strategies build capacity, system strategies provide structural support, and parent strategies enhance relational trust, collectively forming an integrated model of value creation.